ANALISIS KESIAPAN ADMINISTRASI PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (STUDI PADA DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASSET KABUPATEN MALANG) - Tyasa, Iqbal Wilda (Jurnal Mahasiswa Perpajakan, 2014)
Law no. 28 year 2009 on regional taxes and retribution assign transferred to the region of tax land and property rural and urban sectors (PBB P2). Because of this Local Governments should prepare all aspects needed to manage the PBB P2. The purpose of this study was to analyze preparedness the Department of Revenue, Management, Finance and Asset (DPPKA) Malang Regency in implementing PBB P2. This study uses descriptive qualitative approach. Research focus is on the administration of the PBB P2 and duties and responsibilities of implementing PBB P2 on DPPKA Malang regency. This study uses data collection techniques such as interviews and documentation. Selected research instruments researchers is interview guides and form of document recording. Researcher used data analysis techniques with a model of Miles and Huberman.The conclusion of this study is DPPKA Malang regency ready to manage the PBB P2 although there are still some deficiencies that will continue to be evaluated and repaired. Suggestions a can be submitted researcher is to give impetus to Malang regent to take A 0.3% rate, increase cooperation at Bank account opening, move rooms Bidang Pendapatan II, send field officers Bidang Pendapatan II for valuation and separating task objection and appeal. Keywords: Local Governments, Prepare Adminitration, tax land and property rural and urban sectors